1993
DOI: 10.1016/s0022-5347(17)36168-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of The Dorsal Nerve of the Penis Evokes Reflex Tonic Erections of the Penile Body and Reflex Ejaculatory Responses in the Spinal Rat

Abstract: An animal model using the spinal rat was characterized. Electrical stimulation of the dorsal nerve of the penis elicited reflex tonic erections of the penile body and reflex bulbospongiosus muscle activity, flips and ejaculations. The tonic erections of the penile body are independent from contractions of the bulbospongiosus muscle and appear to be the result of a neurovascular process. Our observations suggest that reflex bulbospongiosus muscle activity, flips and ejaculations are a single complex reflex resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
7

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 23 publications
7
47
0
7
Order By: Relevance
“…[18][19][20][22][23][24] The present study has shown that both the renewal and original SS-cream Ⓡ significantly prolonged the BCRLT 10, 30 and 60 min after the application on glans penis of rabbits, and that BCRAP also has decreasing tendency, al- These two pathways may help in controlling over ejaculatory reflex in patients with PE. 16,17,21,25 In this study,the BCR responses to the electric stimulation at the glans penis of rabbit were found to be affected by application of renewal SS-cream Ⓡ on glans penis, and this methods could serve as a useful aminal model for evaluating ejaculatory dysfunction.…”
Section: -17mentioning
confidence: 74%
“…[18][19][20][22][23][24] The present study has shown that both the renewal and original SS-cream Ⓡ significantly prolonged the BCRLT 10, 30 and 60 min after the application on glans penis of rabbits, and that BCRAP also has decreasing tendency, al- These two pathways may help in controlling over ejaculatory reflex in patients with PE. 16,17,21,25 In this study,the BCR responses to the electric stimulation at the glans penis of rabbit were found to be affected by application of renewal SS-cream Ⓡ on glans penis, and this methods could serve as a useful aminal model for evaluating ejaculatory dysfunction.…”
Section: -17mentioning
confidence: 74%
“…For instance, because the rat pelvic and penile vascular anatomy and neuroanatomy have been carefully described 44,45 and show resemblances to those of humans, further penile erection ®ndings relating to anatomical observations in rats could be associated with human situations. Likewise, functional characterizations in the rat, such as sensory re¯exive properties that subserve sexual responses 46,47 and motor activities of the striated penile muscles that are responsible for penile rigidity, 48 which are also described on the human level 2,49 suggest that related studies in the rat could reveal aspects of human erection physiology. Ultimately, while investigators in this ®eld may select an animal model for study after reconciling certain experimental advantages and disadvantages, they may still contend with questions relating to human relevance.…”
Section: Human Relevance Of Animal Modelsmentioning
confidence: 99%
“…Ces neurones commandent la relaxation des fibres musculaires lisses des cloisons trab6culaires circonscrivant les espaces sinusoides des corps caverneux, et des fibres musculaires lisses de la paroi des art~res vascularisant le tissu 4rectile [1]. [14,15,20]. Des stimulations tactiles de la verge et de la peau p~rin~ale sont ainsi capables de provoquer une activation des neurones pro~rectiles parasympathiques de la moelle sacr~e.…”
Section: Organisation De L'innervation Penienne Assurant La Comman Dunclassified
“…Ces derni~res sont tr~s mal connues au plan neurophysiologique. Les ~rections r~flexes persistent chez l'animal apr~s section compl&e de la moelle au niveau suprasacr~ [11,15,18]. Dans cette situation, le seuil de stimulation lib~rerait le centre sacr~ de l'inhibition supraspinale s'exer~ant sur la boucle r~flexe.…”
Section: Les Differents Types D'erec-tion Donnees Experimentaiesunclassified